Biological control under climate change: Distribution patterns of the South American fruit fly, Anastrepha fraterculus and two of its parasitoids in the Americas - Jesús H. Gómez-Llano; Fábio L. Galvão-Silva; Flor E. Acevedo; Fabio Castro-Llanos; Marco Silva Gottschalk; Dori Edson Nava (PLoS ONE, 2025)
Climate change affects the distribution of insects, such as pests and parasitoids. Species Distribution Models (SDMs) have been developed to determine distribution patterns and risk areas for pests and biological control agents under different climate change scenarios. The South American fruit fly, Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae), is an important pest of cultivated fruits throughout the Americas that can be controlled by natural enemies, such as the native parasitoid Doryctobracon areolatus (Szépligeti) (Hymenoptera: Braconidae) and the introduced parasitoid Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae). However, the control efficacy and parasitism performance of these organisms could be affected by changing environmental conditions. SDMs were conducted using Random Forest to predict suitable areas for the establishment of A. fraterculus, D. areolatus, and D. longicaudata under different climate scenarios or Representative Concentration Pathways (SSPs) (SSP 2–4.5 and 5–8.8) in two different periods (2021–2040 and 2041–2060). Our results predicted an increase in suitable areas for A. fraterculus in the Americas, especially in some South American countries such as Colombia and Brazil. Moreover, the projected distribution of these species is intricately linked to the regional climatic patterns. Temperate and tropical areas were more suitable for the establishment of A. fraterculus; D. areolatus was better suited to temperate climates; while tropical climates were more suitable for D. longicaudata. Suitable areas for the establishment of both parasitoid species were predicted to increase in future climate scenarios, with D. longicaudata having a greater geographical expansion than D. areolatus. These parasitoids could be used as biocontrol agents in almost all areas suitable for the establishment of A. fraterculus.